# Besell's Equation

Not what you're looking for? Search our solutions OR ask your own Custom question.

Bessel's Equation:

(a) x^2y" + xy' + (x^2 - n^2)y = 0.

Write the solution as:

(b) y(x) = Sum lambda = 0, a_lambda * x ^ (lamda = k)

Substituting (b) into (a) yields:

Sum lambda = 0, a_lambda * [(k + lambda)(k + lamdba - 1) + (k + lamdba) - n^2]*x^(k + lamda)

+ Sum lamdba = 0, a_lambda * x ^ (lambda + k + 2)

= 0

https://brainmass.com/physics/power/besell-equation-504948

#### Solution Preview

Please see the attachment for the full solution.

We are given Bessel's ...

#### Solution Summary

We derive a power series expansion for the nth order Bessel function from Bessel's differential equation.

$2.49